How toxic environments influence well-being of cervids, and further perspectives for cervid monitoring in Europe - Korzekwa, A.J.; Kowalik, M.K.; Boztepe, G.; Gogola-Mruk, J.; Ptak, A. (Polish Journal of Veterinary Sciences, 2026)
This review provides an exhaustive overview of the main cervid species in Europe, including the red deer (Cervus elaphus), roe deer (Capreolus capreolus), fallow deer (Dama dama), moose (Alces alces) and reindeer (Rangifer tarandus) regarding the geographic distribution of the species, population trends, habitat preferences, and key biological traits. The review focuses on the environmental factors that influence the well-being of cervids, such as habitat quality, competition, food availability, climate change, contamination and anthropopression. Cervids are considered effective bioindicators of ecosystem stability and environmental contamination due to their status as large herbivores with wide-ranging territories and sensitivity to biotope changes. In addition, the impact of perfluoroalkyl and polyfluoroalkyl substances (PFAS) and polychlorinated biphenyls (PCBs) on the well-being of this taxonomic family is characterized. It is imperative to emphasize the significance of incorporating prey, predators, and humans as a comprehensive ecosystem within which cervids reside. The significance of habitat sharing is well documented, particularly in regard to the definition of predator–prey mechanisms. The insights derived from this research are of particular relevance when seeking to define solutions that optimize human-wildlife coexistence, especially within the context of European highly anthropogenic systems. The review concludes with a view on future perspectives for cervid well-being in Europe and emphasizes the necessity of sustainable land use, pollution mitigation, and the establishment of conservation programs for cervid populations and the ecosystems they represent. Effective management requires long-term monitoring, including significant fluctuations and behaviour of the species.